COVID-19 Lockdowns and Decline in Traffic Accidents: Compression between Abu Dhabi and Dubai Emirates - AlAmeri, Jamal Salem Abdulla; Alomosh, Ahmad Falah (Al-Adab Journal, 2023)
Despite the tireless efforts made by the concerned authorities in the UAE to reduce road accidents and reduce injuries, there are still alarming numbers of road accidents and the injuries they cause, leaving grave psychological, social, and economic effects. This study aimed to identify the impact of home quarantine during the Corona pandemic (Covid 19) on the number of injuries caused by traffic accidents in the Emirates of Abu Dhabi and Dubai. And also to identify the differences between the cities of Abu Dhabi and Dubai in the number of injuries caused by traffic accidents during the months of home quarantine in the year 2020 and the corresponding in the years 2015-2019. As well as the differences between the cities of Abu Dhabi and Dubai in the number of injuries caused by traffic accidents during the years (2015-2020). This study relied on the data issued by the Traffic and Patrols Directorate in the United Arab Emirates on accident injuries (simple - moderate severity - death) for the years 2015-2020 according to the months. This study showed a decrease in the number of injuries caused by road accidents during the period of home quarantine in the Emirates of Abu Dhabi and Dubai. The Emirate of Abu Dhabi witnessed a higher number than the Emirate of Dubai in injuries caused by traffic accidents during the home quarantine period to combat the Corona Covid-19 pandemic in 2020, and the Emirate of Abu Dhabi also witnessed an increase in the total number of injuries caused by traffic accidents during all the years since 2015 to 2020.